2016
DOI: 10.1371/journal.pone.0163664
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Species Delimitation Based on Phylogenetic Analyses: A Case Study in the Hypogymnia hypotrypa Group (Parmeliaceae, Ascomycota)

Abstract: Delimiting species boundaries among closely related lineages often requires a range of independent data sets and analytical approaches. Similar to other organismal groups, robust species circumscriptions in fungi are increasingly investigated within an empirical framework. Here we attempt to delimit species boundaries in a closely related clade of lichen-forming fungi endemic to Asia, the Hypogymnia hypotrypa group (Parmeliaceae). In the current classification, the Hypogymnia hypotrypa group includes two speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Similar to other lichen genera and species complexes (e.g., Leavitt et al 2011cLeavitt et al , 2016Lücking et al 2014), including Peltigera sections Polydactylon and Peltigera, where the proportion of undiscovered biodiversity was unexpectedly high (half or more of the recovered species were potentially new; Magain et al 2017aMagain et al , b, 2018 support the recognition of 14 putative species for section Peltidea, of which nine are undescribed. The impact of the incongruence among loci and implemented methods on currently recognized species has previously been reported across various taxonomic groups, including fungi and, among them, the genus Peltigera (e.g., Singh et al 2014 and references therein;Wei et al 2016;Magain et al 2017a, b, 2018 andreferences therein;Da Silva et al 2018). In this study we detected a relatively high level of discrepancy and uncertainty in the species number and species boundaries, including cases of paraphyletic/polyphyletic entities, as well as nested and singleton species, especially in P. aphthosa (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to other lichen genera and species complexes (e.g., Leavitt et al 2011cLeavitt et al , 2016Lücking et al 2014), including Peltigera sections Polydactylon and Peltigera, where the proportion of undiscovered biodiversity was unexpectedly high (half or more of the recovered species were potentially new; Magain et al 2017aMagain et al , b, 2018 support the recognition of 14 putative species for section Peltidea, of which nine are undescribed. The impact of the incongruence among loci and implemented methods on currently recognized species has previously been reported across various taxonomic groups, including fungi and, among them, the genus Peltigera (e.g., Singh et al 2014 and references therein;Wei et al 2016;Magain et al 2017a, b, 2018 andreferences therein;Da Silva et al 2018). In this study we detected a relatively high level of discrepancy and uncertainty in the species number and species boundaries, including cases of paraphyletic/polyphyletic entities, as well as nested and singleton species, especially in P. aphthosa (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Regardless of the focus group and sequenced loci, most studies implementing species delimitation and validation methods revealed multiple undescribed species with much narrower geographic ranges than traditionally circumscribed morphospecies, whereas an overestimation of species richness based on phenotypic traits was rarely reported. Most importantly, molecular phylogenetics enables the reevaluation of characters regarded as taxonomically important (e.g., Leavitt et al 2011aLeavitt et al , b, c, 2013Lücking et al 2014;Saag et al 2014;Singh et al 2015;Kirika et al 2016 and references therein; but see Wei et al 2016). For example, in the scabrosoid clade of section Polydactylon, seven of ten delimited species were putatively new, whereas in the dolichorhizoid clade 22 potentially new species were delimited for a total of 27 (Magain et al 2017a, b).…”
Section: Introductionmentioning
confidence: 99%
“…2015; Wei et al . 2016; Garrido-Benavent et al 2017). It is generally assumed that GMYC overestimates the species diversity and that its results are greatly influenced by the sampling (Satler et al .…”
Section: Discussionmentioning
confidence: 99%
“…Uneven sampling has also been linked to poor performance and conflict between delimitation methods (Lim & al., 2012; Rittmeyer & Austin, 2012) and likely explain some of the incongruences detected. In lichenized fungi, conflict between delimitation methods has also been attributed to limitations in placing boundaries in lineages with recent diversification histories (Wei & al., 2016). This might have affected delimitation within S .…”
Section: Discussionmentioning
confidence: 99%